Cities, biodiversity and health: we need healthy urban microbiome initiatives. Issue 2 (30th November 2018) - Flies, Emily J.; Skelly, Chris; Lovell, Rebecca; Breed, Martin F.; Phillips, David; Weinstein, Philip
ABSTRACT: Current evidence suggests that biodiverse environmental microbiomes contribute positively to human health and could account for known associations between urban green space and improved health. We summarise the state of knowledge that could inform the development of healthy urban microbiome initiatives (HUMI) to re-connect urban populations to biodiverse microbial communities.